Enhancing Capacity of Health Workers and Community Health Cadres in Preterm Infant Care Through Behavior Change Communication: A Community-Centric Training Initiative in Bandung District - Mira Miraturrofiah; Qorinah Estiningtyas Sakilah Adnani; Dwi Agustian; Yanyan Mulyani; Citra; Niknik Nursifa; Hana Nurhanifah; Ika Khairunnisa; Wenny Desmana; Nenden Nurul Aulia; Dany Hilmanto (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2026)
Background: Preterm birth, characterized as childbirth prior to 37 weeks of gestation, continues to pose a significant challenge in mother and child health due to the heightened susceptibility of preterm newborns to complications, including respiratory issues, hypothermia, infections, feeding difficulties, and developmental issues. Efficient post-discharge care is crucial to avert difficulties and hospital readmissions; nevertheless, numerous families possess insufficient knowledge and abilities to care for preterm newborns at home. Enhancing the capabilities of healthcare professionals and community health workers is essential to support families and maintain treatment continuity, thereby improving families’ ability to provide appropriate home care for preterm infants and reducing the risk of complications and readmissions. Aims: This study sought to enhance the capabilities of health workers and community health cadres to assist families of preterm children through a Behavior Change Communication (BCC)-oriented mentorship strategy in Bandung Regency, Indonesia. Methods: This community-oriented program employed a participatory capacity-building training methodology, engaging 69 participants, including 23 midwives and 46 community health workers from 23 primary health facilities. The program was delivered over three days, utilizing a blended learning strategy that integrated online lectures, workshops, discussions, simulations, role-playing, and skill-based practice stations. Knowledge enhancement was evaluated by pre-test and post-test assessments. Results: The findings indicated a significant enhancement in participants' understanding. The percentage of cadres with adequate knowledge rose from 58.7% to 91.3%, while among health workers it increased from 65.2% to 91.3%. Knowledge scores enhanced in 89.1% of cadres and 87.0% of health workers. Conclusion: The findings demonstrate that participatory training, which combines clinical care and behavior change communication, effectively enhances the capabilities of health workers and community cadres to support families in the home care of preterm newborns.